Compilation of Financial Accounts in the OECD Countries - Quinteros Massardo, Denisse Sofia (2020)
Nowadays, the importance of National Accounts is the key to understanding the behaviour of modern financial institutions. The aim of this report is to review different methodologies of National Account in the European Union, the United States and Chile, and to describe the relation of the financial accounts in the institutional sectors in the selected countries: the Czech Republic, Germany, United Kingdom, United States and Chile. All countries member of the OECD. This was analysed with respect to the assets and liabilities in the stock (balance sheets) and flows (transactions). It is possible to observe how the countries near the Czech Republic exhibit similar behaviour. This report was initially created by comparing the Czech Republic and the United Kingdom as an example of differences in the structure in the balance sheets and financial transactions. In this report, it is also possible to observe that the changes in the flows were significant in the crisis period and the Gini coefficient that brings the idea of distribution of the wealthiest in a country.